Anaesthetic Management of Liver Resection Surgery in Birendra Army Hospital - KC, Nagendra Bahadur; Rai, Sashi; Panta, Sunita (Medical Journal of Shree Birendra Hospital, 2010)
This is a case report of a 65 yrs old male patient who underwent resection of left lateral segment (segment 2- 3) of Liver for advanced Hepatocellular carcinoma. The case was performed under general anesthesia combined with epidural analgesia for post op pain management. During resection, Hypotension is maintained to reduce bleeding. Key words: Blood and CVP pressure; Epidural analgesia; General Anesthesia; Hepatocellular carcinoma (HCC); left lateral segmentectomy DOI: 10.3126/mjsbh.v9i1.3487 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 24-27